2013
DOI: 10.1016/j.euroneuro.2012.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Sustained incentive value of heroin-related cues in short- and long-term abstinent heroin users

Abstract: Models of addiction and addiction memory propose that drug-associated cues elicit incentive effects in drug users, which play an important role in maintenance of drug use and relapse. Incentive effects have been demonstrated for smoking and alcohol-related cues but evidence for heroin-related cues has been inconclusive. Furthermore, it is unknown whether appetitive effects of heroin-related cues persist after prolonged abstinence, although heroin addiction is known to have high relapse rates. Therefore, we inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 51 publications
2
16
0
Order By: Relevance
“…Heroin-associated cues are shown to play an important role in the maintenance of drug use and relapse (Carter and Tiffany, 1999;Preller et al, 2013), also after a long period of abstinence (Preller et al, 2013). In line with this, it has been reported that cue-reactivity as measured with intracranial electroencephalography (EEG) recordings was related to NA DBS effectiveness for heroin dependence at the same contact points of the DBS electrodes (Valencia-Alfonso et al, 2012).…”
Section: Differential Role Of Nacore and Nashell In Expression Of Hersupporting
confidence: 51%
“…Heroin-associated cues are shown to play an important role in the maintenance of drug use and relapse (Carter and Tiffany, 1999;Preller et al, 2013), also after a long period of abstinence (Preller et al, 2013). In line with this, it has been reported that cue-reactivity as measured with intracranial electroencephalography (EEG) recordings was related to NA DBS effectiveness for heroin dependence at the same contact points of the DBS electrodes (Valencia-Alfonso et al, 2012).…”
Section: Differential Role Of Nacore and Nashell In Expression Of Hersupporting
confidence: 51%
“…The lack of attention modulation in response to drugrelated cues has been reported in studies comparing treatment-seeking and non-treatment-seeking individuals with CUD, 50 satiated and abstinent chronic smokers, 51 and short-and long-term abstinent heroin users. 52 These studies suggest that even after longer durations of reduced drug use, responsiveness to drug-related cues stays elevated perhaps owing to longterm pairing of the cues (i.e., pipes of crack-cocaine, other paraphernalia) with the actual drugs. This inability to divert attention away from drug-related cues has been interpreted to mark enhanced personal relevance and could reflect a strong desire to avoid drug-related cues, 53 potentially suggesting an increased motivation to quit/remain abstinent in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The incentive value of heroin-related cues has been reported to be sustained in heroin misusers even after prolonged abstinence [48]. The results of our study have practical implications; they point to the importance of including cognitive strategy training to reduce the impact of heroin-related cues as part of relapse prevention programmes [48,49]. Assisting heroin misusers in identifying the negative consequences of drugs may help to devalue the expected drug effects.…”
Section: Discussionmentioning
confidence: 72%
“…This study also suggests that the incentive value of heroin-related cues strongly influences the AHMs' decision-making, even though they may exhibit intact decision-making performance. The incentive value of heroin-related cues has been reported to be sustained in heroin misusers even after prolonged abstinence [48]. The results of our study have practical implications; they point to the importance of including cognitive strategy training to reduce the impact of heroin-related cues as part of relapse prevention programmes [48,49].…”
Section: Discussionmentioning
confidence: 73%